2022
DOI: 10.3389/fonc.2022.970286
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Unique ultrasound feature of thyroid metastases in occult breast cancer

Abstract: Occult breast cancer is an uncommon type of breast cancer. Metastases of occult breast cancer to other tissues are rather rare. We present a rare case of thyroid metastases in a 46-year-old woman who underwent occult breast cancer. The first ultrasound (US) examination of the thyroid showed that the left lobe was enlarged but had normal thyroid function. At first, this case was misdiagnosed as thyroiditis based on the thyroid US features. However, the cytological and histological results showed that nests of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to previous literature and case reports, the most common sites of pathological diagnosis or metastasis were the axilla, bone, and orbit. Meanwhile, some uncommon sites had also been reported, including gastrointestinal tract, liver, lung, thyroid, and brain (8)(9)(10). OBC patients with distant metastatic disease have a much worse prognosis, with a 5-year survival of 14.3% (8).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous literature and case reports, the most common sites of pathological diagnosis or metastasis were the axilla, bone, and orbit. Meanwhile, some uncommon sites had also been reported, including gastrointestinal tract, liver, lung, thyroid, and brain (8)(9)(10). OBC patients with distant metastatic disease have a much worse prognosis, with a 5-year survival of 14.3% (8).…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of TMs are metachronous [ 20 ], detected after a mean time of 2.3 years in head and neck cancers [ 10 , 21 ], a mean time of 9.4 years in renal cell carcinoma [ 22 ], and even after 21 years in intestinal neuroendocrine tumors [ 23 ]. In our literature review, we found 38 papers published between 2000 and the end of January 2023 that satisfied our search criteria, consisting of 58 cases of TM that originated from BC [ 5 , 9 , 11 , 17 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. We summarized the cases in Table 2 .…”
Section: Current Knowledgementioning
confidence: 99%